Mössbauer spectroscopy and X-ray diffraction studies of ball-milling-induced transformations of a near-equiatomic FeV sigma phase: Influence of oxygen - Costa, B. F. O. (2007)
57Fe Mössbauer spectroscopy and X-ray diffraction were used to study the structural changes induced by ball milling a coarse-grained Fe48.1V51.9 at% sigma phase in a vibratory mill in argon with a frequent gas renewal. The sigma phase transforms into a bcc alpha phase till 140 h of milling. Mössbauer spectroscopy also shows the presence of an amorphous phase. Further, X-ray diffraction and Mössbauer spectroscopy reveals the presence of a corundum type oxide (V1-xFex)2O3 and of a spinel FeV2O4 in samples milled for 140 h and longer. Mössbauer spectroscopy clearly shows that the spinel phase starts to form after 140 h of milling. Oxidation is progressive and occurs first via an unmixing process which deprives the FeV bcc matrix of vanadium atoms.